2022
DOI: 10.1108/jcm-02-2021-4439
|View full text |Cite
|
Sign up to set email alerts
|

If tomorrow never comes: the impact of anxiety, materialism and attitude on consumption behavior in a pandemic

Abstract: Purpose This research aims to examine the impact of consumers’ anxiety on the three types of consumption activities (sharing, hoarding and regular buying) during the coronavirus pandemic. Further, it aims to investigate the moderating role of materialism on anxiety and how attitude toward the pandemic affects consumers’ consumption behavior. Design/methodology/approach An online survey was conducted to test the proposed research model. The data were analyzed using SmartPLS and PROCESS tools. Findings Highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 71 publications
(182 reference statements)
1
18
0
Order By: Relevance
“…And, extraversion is also associated with well-being and loneliness when the curfew was imposed during the pandemic. Likewise, research also revealed that a higher level of materialism was highly related to attitude towards anxiety and lockdown [ 232 ]. Though materialism and extraversion had an impact on the usage of social mobile applications [ 233 ], people used social media to involve themselves to disclose information and stay connected during the Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And, extraversion is also associated with well-being and loneliness when the curfew was imposed during the pandemic. Likewise, research also revealed that a higher level of materialism was highly related to attitude towards anxiety and lockdown [ 232 ]. Though materialism and extraversion had an impact on the usage of social mobile applications [ 233 ], people used social media to involve themselves to disclose information and stay connected during the Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Tata et al [ 32 ], developed an integrated model applying personality traits, and intrinsic-extrinsic motivational drivers in predicting e-WOM behaviour. Later, knowing the significance of consumers' behaviour during the pandemic, Mishra et al [ 232 ], argued the moderating role of materialism on the association between anxiety and attitude towards consumption. Arguing in the same line, Moldes et al [ 243 ], observed the increase in level of materialism during the pandemic owing to anxiety, stress, and excessive media consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review reveals that infodemic adversely impacted several sectors such as transportation, tourism, education and healthcare. The ridesharing sector is yet another one that has suffered the effects of infodemic despite ride-hailing companies' assurances about following standard operating procedures and taking safety precautions (Mishra et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For retailers, such behaviours represent additional financial risks in already challenging crisis-dominant environments (Ferraro et al, 2022;Raassens et al, 2021) as they disrupt operations, waste resources, cause stress and negatively impact customers' shopping behaviour. Looking at the most recent crisis situation, media reports reveal that customers did not always behave as desired, displaying patterns of hoarding behaviour (Gupta et al, 2021;Mishra et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Looking at the most recent crisis situation, media reports reveal that customers did not always behave as desired, displaying patterns of hoarding behaviour (Gupta et al. , 2021; Mishra et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%